The Impact of Covid-19 Pandemic on the Stock Market Performance: A Study on Dhaka Stock Exchange (DSE) - Hossain, Tarik; Nesa, Taslimun; Dowla, Md Shaikh Ud; Akter, Farjana (International Journal of Business, Economics and Management, 2021)
The endemic of the COVID-19 pandemic caused by coronavirus has stroked everywhere of the world, including capital markets. This research intends to examine the effect of the COVID-19 pandemic on the performance of stock markets of Bangladesh. For this purpose, daily panel data from March 01, 2020, to June 27, 2021, a total number of 286 days’ data have been used. The influence of Covid-19 on the DSE has been quantified by regression analysis using DSE indexes like DSEX and DSE30 as the dependent variables. Daily new confirmed cases and deaths of the world and Bangladesh, lockdown imposed in Bangladesh are used as the independent variables. Inflation rate, bank rate, interest rate of deposit, interest rate of loan and advance, exchange rate, and gold price are used as the control variables. The study found an alarming impact of the Covid-19 pandemic on the stock market indexes of DSE. The daily new confirmed cases of the world and Bangladesh, Bank rate, inflation rate, interest rate of deposit has a significant negative impact on the DSE indices, while the daily deaths in the world and Bangladesh, interest rate of loan and advance, and gold price has a significant positive relationship with DSE indices. This study also found that lockdown imposed in Bangladesh for controlling the Covid-19 is significant negatively related with DSEX index and significant positively related with DSE30 index. The recommendations will help the investors, policymakers, regulatory authority, and governments to make proper decisions for combating the pandemic crisis.